Recent Advanced Biological Wastewater Treatment Technologies - Linh Thy, Le; Huu Viet, Nguyen; Xuan Thanh, Bui (VNU Journal of Science: Earth and Environmental Sciences, 2024)
Conventional wastewater treatment approaches such as activated sludge processes often rely on energy-intensive and resource-demanding processes. However, emerging technologies offer promising solutions to improve the sustainability of wastewater management. This review examines three innovative technologies, including anaerobic membrane bioreactor (AnMBR), partial nitritation/anammox (PN/A), and microalgae-based processes, and their potential advantages over traditional methods. AnMBR combine membrane filtration with anaerobic biological treatment, enabling high-quality effluent, reduced sludge production, and a compact footprint. The PN/A is a two-step biological process that can achieve efficient nitrogen removal with lower aeration requirements. Microalgae-based systems leverage photosynthetic organisms to remove nutrients and organic matter while generating biomass for potential resource recovery. Each alternative technology has strengths and limitations that must be carefully evaluated based on the site-specific factors, such as wastewater characteristics, treatment objectives, and local conditions. Continued research and technological development is necessary to address the remaining technical and economic barriers impeding their wider adoption. Integrating multiple alternative technologies in a treatment train can help optimize overall performance by leveraging the complementary advantages of different processes. This holistic approach can advance the sustainable wastewater management, promoting resource efficiency, energy savings, and environmental protection.